2010
DOI: 10.1111/j.1469-8986.2010.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid induction reduces N400s of healthy subjects with delusional‐like ideation

Abstract: A previous study suggests that the amplitude of the N400 event-related potentials (ERPs) of healthy subjects does not vary with their delusional-like ideations. This contrasts with the smaller N400 amplitudes observed in more- than in less-deluded schizophrenia patients. Here, we hypothesize that these smaller N400 amplitudes were related to the paranoid feelings patients had during the ERP recording. We thus induced this type of feelings in healthy subjects. Delusional-like ideation was assessed with the schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 72 publications
5
13
0
Order By: Relevance
“…This was particularly the case for participants who scored highly on the ''interpersonal'' scale, one component of which is paranoid ideation. This result is consistent with the work of Mucci et al (2005) in showing reduced 238 BOURNE AND McKAY lateralisation in individuals with paranoia, although Prevost et al (2011) did not consider possible sex differences in their findings. Nunn and Peters (2001) looked at the relationship between language lateralisation and scores on the various scales of the O-LIFE measure of schizotypy (Oxford-Liverpool Inventory of Feelings and Experiences: Mason, Claridge, & Jackson, 1995) in a non-clinical sample.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…This was particularly the case for participants who scored highly on the ''interpersonal'' scale, one component of which is paranoid ideation. This result is consistent with the work of Mucci et al (2005) in showing reduced 238 BOURNE AND McKAY lateralisation in individuals with paranoia, although Prevost et al (2011) did not consider possible sex differences in their findings. Nunn and Peters (2001) looked at the relationship between language lateralisation and scores on the various scales of the O-LIFE measure of schizotypy (Oxford-Liverpool Inventory of Feelings and Experiences: Mason, Claridge, & Jackson, 1995) in a non-clinical sample.…”
supporting
confidence: 94%
“…Second, it suggests that there may be sex differences in the relationship between non-clinical levels of schizotypic traits and lateralisation. In another study, using event related potentials, a reduction in the left N400 response was found when a state of paranoia was induced (Prevost et al, 2011). This was particularly the case for participants who scored highly on the ''interpersonal'' scale, one component of which is paranoid ideation.…”
mentioning
confidence: 96%
“…These results are at odds with the findings of Debruille et al (2007) and Kiang et al (2007) in schizophrenia patients and could be used to support a distinction between normal population and schizophrenia patients in contrast with the idea of a continuum between the two (Garety, Bebbington, Fowler, Freeman, & Kuipers, 2007; Shevlin et al, 2007; Verdoux & van Os, 2002). However, the results of Prévost, Rodier, Lionnet, Brodeur, King, and Debruille (forthcoming) suggest that smaller N400s can be found in healthy subjects with high scores on delusion‐like ideation items of the SPQ, when boosting paranoid feelings, which probably diminishes some of the differences between schizophrenia patients and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of SP abnormalities has been found to be correlated with that of several clinical features: TD, positive symptoms, delusional‐like ideation, as well as with negative symptoms …”
mentioning
confidence: 99%